Scripting Control: Computer Choreography and Neoliberal Performance. - Eacho, Douglas (Theatre Journal, 2021)
From 1964 to 1978, three artists—Jeanne Beaman, John Lansdown, and Analívia Cordeiro—gave their choreographic practices over to computer software. Their dances were the first theatrical performances scored by digital computers. This essay outlines these figures' forgotten histories and argues that they developed a neoliberal performance aesthetic. Computer choreography was a metaphor for governance by aleatory management. The conjunction of an algorithmic score and the human performer internalized the vagaries of the constructed market and presented them as a spontaneously emergent self. The performance of computational scores thus became a stage for harmonizing the body with market patterns. For Beaman and Lansdown, faith in the computer's futurity overrode any concerns over what that futurity might bring about. Cordeiro, by contrast, made early and trenchant critiques of this logic, situated within her experience of dictatorial Brazil. Troublingly, one of her dances employed blackface to articulate her critique, prompting attention to how anti-Blackness can structure reactions to neoliberalism. Early computer choreography thus redirects scholarship on digital performance from posthumanism to a historical materialist study of performance's deployment in the capitalist phase computation made possible.